2022
DOI: 10.1002/1878-0261.13188
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA predicts efficacy of a dual AKT/p70S6K inhibitor (LY2780301) plus paclitaxel in metastatic breast cancer: plasma analysis of the TAKTIC phase IB/II study

Abstract: The phosphatidylinositol-3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway is frequently activated in HER2-negative breast cancer and may play a role in taxane resistance. The phase IB/II TAKTIC trial (NCT01980277) has shown that combining a dual AKT and p70 ribosomal protein S6 kinase (p70S6K) inhibitor (LY2780301) taken orally with weekly paclitaxel in HER2-negative advanced breast cancer is feasible, with preliminary evidence of efficacy. We wanted to explore whether circulating tumor DNA (ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“… Mutation detection before neoadjuvant anti-HER2 therapies is associated with decreased pathological complete response. Sabatier et al, 2022 [ 121 ] R88Q, E542K, E545K, H1047L, H1047R, and TP53 and AKT1 mutations HER2 negative metastatic breast cancer ctDNA as surrogate marker of treatment efficacy within the phase IB/II TAKTIC trial in which patients received dual AKT and p70 ribosomal protein S6 kinase inhibitor in combination with paclitaxel. Progression-free survival at 6 months 92% for mutation negative patients and 68% for mutation positive cases at baseline.…”
Section: Use Of Digital Pcr In Ctdna Analysis In Breast Cancer Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“… Mutation detection before neoadjuvant anti-HER2 therapies is associated with decreased pathological complete response. Sabatier et al, 2022 [ 121 ] R88Q, E542K, E545K, H1047L, H1047R, and TP53 and AKT1 mutations HER2 negative metastatic breast cancer ctDNA as surrogate marker of treatment efficacy within the phase IB/II TAKTIC trial in which patients received dual AKT and p70 ribosomal protein S6 kinase inhibitor in combination with paclitaxel. Progression-free survival at 6 months 92% for mutation negative patients and 68% for mutation positive cases at baseline.…”
Section: Use Of Digital Pcr In Ctdna Analysis In Breast Cancer Patientsmentioning
confidence: 99%
“…ctDNA status at week 7 was informative on prognosis. The authors concluded that plasma-based ctDNA analysis may be useful in identifying alterations contributing to resistance development to therapy [ 121 ]. The impact of PIK3CA hotspot mutations (H1047R, E545K, and E542K) was also assessed on the everolimus efficacy, an mTOR inhibitor, in the BOLERO-2 trial by ddPCR.…”
Section: Use Of Digital Pcr In Ctdna Analysis In Breast Cancer Patientsmentioning
confidence: 99%
See 2 more Smart Citations